(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: The aim of this study was to determine the effect of ice cream combination with yogurt. and the use of sucrose levels on melting power, yogurt ice cream was made from goat's milk. Methods: The design which was used is a complete rendomized design 5 x 5 factorial pattern with 3 repeats. Results: The result of variety analysis showed that the treatment of adding sucrosa levels, the treatment of ice cream dough combination with yogurt and the interaction between the two treatments had a very real effect (P<0,01) towards melting power, sweetness, texture. Based on the result of the study was concluded that the higher addition of sucrose to yogurt affect on sweetness, texture, but the content melted power decreases. the higher ratio of yogurt in combination of yogurt ice cream on melted power, sweetness, texture decreases.